Do team gymnasts compete in spite of symptoms from an injury? - Harringe, M. L.; Lindblad, S.; Werner, S. (British Journal of Sports Medicine, 2004)
Background: Gymnasts practise many hours a week, and symptoms from injuries do not seem to stop them from continuing with practice. They may even compete with symptoms from injuries, which could increase the risk of reinjury, or of the occurrence of a more severe injury.